78 Proceedings of the Conventions of the Province of Maryland, 1774-1776, at 20 (1836); see also 1777 Md. Laws ch. 17 - (:unkn) unknown (My University, 1775)
Required "[t]hat every able bodied effective freeman within this province, between sixteen and fifty years of age . . . enroll himself in some company of militia." Further retained the new maximum of 50 years and excluded non-whites.
Keywords: MILITIAS